Effects of Aloe vera as Leaf Protein Concentrate on Growth Performance of Cockerels - Odo, B.I.; Ekenyem, B.U.; Nwamo, A.C. (International Journal of Poultry Science, 2010)
The study investigated the effects of Aloe vera as leaf protein concentrate for cockerels. It was conducted with 72 - day old cockerels which at 3 weeks of age were randomly allotted to 3 dietary treatments of 24 birds each with 3 replicates per treatment. The rations were standard commercial feed 0% (T1), 5% (T2) and 10% (T3) inclusion levels of Aloe vera respectively. The design of the experiment was a completely randomized design and the birds were fed for 42 days with their respective experimental diets. Records were kept on feed intake, body weight gain, feed conversion ratio and mortality trend to the end of the experiment. Results showed that there were significant differences (p0.05) on feed intake. Highest overall profit was obtained from the T2 group. The inclusion of Aloe vera at 5% level supports feed absorption and growth in cockerels. This can therefore be used as a good leaf protein concentrate in cockerel nutrition for improved productivity and therefore, profitability.